2021
DOI: 10.1371/journal.pone.0259842
|View full text |Cite
|
Sign up to set email alerts
|

Use of universal primers for the 18S ribosomal RNA gene and whole soil DNAs to reveal the taxonomic structures of soil nematodes by high-throughput amplicon sequencing

Abstract: Nematodes are abundant metazoans that play crucial roles in nutrient recycle in the pedosphere. Although high-throughput amplicon sequencing is a powerful tool for the taxonomic profiling of soil nematodes, polymerase chain reaction (PCR) primers for amplification of the 18S ribosomal RNA (SSU) gene and preparation of template DNAs have not been sufficiently evaluated. We investigated nematode community structure in copse soil using four nematode-specific (regions 1–4) and two universal (regions U1 and U2) pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…For instance, our results are in agreement with previous studies that used mock communities to compare the performance of MMSF-MMSR, NemF-18Sr2b, NF1_18Sr2b and SSU_F04-SSU_R22, and observed a limited coverage of SSU_F04-S-SU_R22 [18,49]. Similarly, Kenmotsu et al [50] confirmed that F_1183-R_1631 and NF1_18Sr2b show a similar, very good performance; Geisen et al [51] confirmed the excellent performance of 3NDf-1132rmod; and Guardiola et al [31] suggested an excellent coverage for Euka02 [see also ref. 36 for in vitro tests confirming the excellent taxonomic coverage of this marker for all the tested invertebrate phyla].…”
Section: Plos Onesupporting
confidence: 93%
“…For instance, our results are in agreement with previous studies that used mock communities to compare the performance of MMSF-MMSR, NemF-18Sr2b, NF1_18Sr2b and SSU_F04-SSU_R22, and observed a limited coverage of SSU_F04-S-SU_R22 [18,49]. Similarly, Kenmotsu et al [50] confirmed that F_1183-R_1631 and NF1_18Sr2b show a similar, very good performance; Geisen et al [51] confirmed the excellent performance of 3NDf-1132rmod; and Guardiola et al [31] suggested an excellent coverage for Euka02 [see also ref. 36 for in vitro tests confirming the excellent taxonomic coverage of this marker for all the tested invertebrate phyla].…”
Section: Plos Onesupporting
confidence: 93%
“…More than four soil samples were isolated from near the plant and mixed together at each sampling point, where the neighbored sampling point was located 35 cm apart. A total of 36 sample soils were isolated from 3 independent sampling points at 2 fields cultivated with 2 crops at 3 growth stages and pretreated before DNA purification, as described previously 34 . This study was carried out in accordance with relevant guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Purified soil DNA was stored at − 20 °C. The 16S (V3–V4 region) and 18S (V7–V8 region) rRNA genes were amplified from soil DNA with the universal primers 16S_Amplicon_MiseqF and 16S_Amplicon_MiseqR (341F and 805R with tail sequences 73 ) and F1183-18S_V7-V8_MiseqF and R1631a-18S_V7-V8_MiseqR 34 , respectively. The PCR mixture (20 μL) contained 10 μL of 2 × Buffer for KOD FX Neo, 4 μL of 2 mM dNTPs, 0.4 units of KOD FX Neo DNA polymerase (Toyobo, Tokyo, Japan), 2 μL of template DNA, and 0.3 mM each of the forward and reverse primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ITS region of the fungi was ampli ed with the primers TS1F (5'-CTTGGTCATTTAGAGGAAGTAA-3') and ITS2 (5'-GCTGCGTTCTTCATCGATGC-3') (Martin and Rygiewicz 2005). For nematodes, PCR reactions used the primers NF1 (5'-GGTGGTGCATGGCCGTTCTTAGTT-3') and 18S r2bR (5'-TACAAAGGGCAGGGACGTAAT-3') to amplify the V4 region of 18S rRNA gene (Kenmotsu et al 2021). Polymerase Chain Reaction (PCR) analysis was performed in triplicate according to the following thermal program: pre-denaturation at 95°C for 5 min, denaturation at 95°C for 30 s, annealing at 50°C for 30 s, extension at 72°C for 40 s, and nal extension at 72°C for 7 min, 25 cycles.…”
Section: Dna Extraction Pcr Ampli Cation and Sequencingmentioning
confidence: 99%